Assessing basic and higher-level psychological needs satisfied through physical activity - Dunton, Genevieve F.; Do, Bridgette; Crosley-Lyons, Rachel; Naya, Christine H.; Hewus, Micaela; Kanning, Martina (Frontiers in Psychology, 2023)
Background: There has been increasing interest in the extent to which the fulfillment of psychological needs is associated with physical activity engagement. However, a vast majority of studies consider only basic psychological needs such as relatedness, competence, and autonomy— with higher-level psychological needs such as challenge, creativity, and spirituality rarely addressed. The aim of this study was to examine the preliminary reliability (i.e., internal consistency) and validity (i.e., discriminant, construct, predictive) of a multi-dimensional scale to assess a range of basic and higher-level psychological needs satisfied through physical activity. Methods: A sample of 75 adults (ages 19-65 years, 59% female, 46% White) completed a baseline questionnaire measuring 13 psychological needs subscales (i.e., physical comfort, safety, social connection, esteem from others, individual esteem, learning, challenge, entertainment, novelty, creativity, mindfulness, aesthetic appreciation, morality), exercise enjoyment, and exercise vitality. Participants then completed 14 days of accelerometer monitoring of physical activity and ecological momentary assessment of affective responses during physical activity sessions in daily life. Results: Internal consistency reliability was acceptable (>.70) for all subscales except for mindfulness, aesthetic appreciation, and morality. Ten of the 13 subscales exhibited discriminant validity by differentiating between engagement (vs. no engagement) in at least one physical activity type (e.g., brisk walking, yoga/Pilates). All the subscales, except physical comfort and esteem from others, were associated with at least one of the construct validation criteria (e.g., exercise enjoyment, affective response during exercise). Five of the subscales were associated with at least one of the predictive validation criteria (i.e., light, moderate, vigorous intensity activity measured by accelerometer). Conclusion: Having the capacity to assess whether one’s current physical activity is failing to fulfill various psychological needs—combined with recommendations about which types of activities may satisfy those needs—may address an important gap in physical activity promotion.